Menggagas Strategi Pemulihan Bagi Anak Korban Konflik Orang Tua di Keluarga Kristiani - Manurung, Kosma (Sekolah Tinggi Teologi Kanaan Nusantara, 2023)
A home filled with peace, love and mutual respect is the dream of every family member. In fact, there are many houses that indicate otherwise. Where fear, anger, hatred, mutual condescension, and physical attacks were exhibited by both parents at home when they were in conflict. If parents' conflicts are examined more deeply, of course, the impact on children can be in the form of loss of peace, destroying happiness, damaging emotions and degrading children's intelligence. This article intends to initiate a recovery strategy for child victims of parental conflict in Christian families. The use of qualitative descriptive methods and support from literature reviews is expected to be able to provide strong, sharp, careful and systematic explanations related to the triggering factors for parental conflict, the impact of parental conflict on children, and recovery strategies for children who are victims of parental conflict in Christian families. The recovery strategies were concluded, namely bringing children to know the truth of the Bible, repenting of parents, treating spouses with love, and asking for professional help.AbstrakRumah yang dipenuhi oleh kedamaian, rasa sayang, dan saling hormat merupakan dambaan setiap anggotanya. Kenyataannya, ada banyak rumah yang justru mengindikasikan sebaliknya. Di mana ketakutan, kemarahan, kebencian, saling merendahkan, hingga serangan fisik dipertontonkan oleh kedua orang tua di rumah ketika mereka sedang berkonflik. Konflik orang tua jika ditelisik lebih dalam, tentunya berdampak pada anak bisa berupa hilangnya damai sejahtera, menghancurkan kebahagiaan, merusak emosi hingga mendegradasi kecerdasan anak. Adapun artikel ini bermaksud menggagas strategi pemulihan bagi anak korban konflik orang tua di kelaurga Kristiani. Penggunaan metode deskriptif kualitatif serta dukungan dari kajian literatur, diharapkan mampu memberikan penjelasan yang kuat, tajam, cermat, dan sistimatik terkait dengan faktor pemicu konflik orang tua, dampak konflik orang tua terhadap anak, dan strategi pemulihan anak korban konflik orang tua di keluarga Kristiani. Disimpulkan strategi pemulihannya yaitu membawa anak mengenal kebenaran Alkitab, pertobatan orang tua, memperlakukan pasangan dengan penuh kasih sayang, serta meminta bantuan tenaga profesional.